UN GUIDING PRINCIPLES ON BUSINESS AND HUMAN RIGHTS: THEORETICAL AND LEGAL BASIS - Arslonova Robiya (Scholar Express Journals, 2025)
The UN Guiding Principles on Business and Human Rights (UNGPs) have become the field’s central lingua franca for allocating responsibilities among states and enterprises to prevent, address, and remedy business-related human rights harms. This article reconstructs the UNGPs’ theoretical architecture and traces their evolving legal basis. Part I situates the UNGPs in their genealogy from the “Protect, Respect and Remedy” framework and the Human Rights Council’s 2011 endorsement to today’s regime complex that blends public and private rulemaking. Part II excavates core ideas polycentric governance, due diligence as a standard of conduct, and the complementarity between state obligations and corporate responsibilities drawing connections to treaty-body doctrine and labor norms. Part III maps pathways of “legalization”: integration into the OECD Guidelines (2023 update), the ILO’s 2022 recognition of a safe and healthy working environment as fundamental, and the rapid diffusion of hard-law instruments, culminating in the EU Corporate Sustainability Due Diligence Directive (Directive (EU) 2024/1760). Part IV analyzes access to remedy judicial and non-judicial alongside judicial trends on parent-company duties of care. Part V canvasses critiques (voluntarism, extraterritoriality, remedy gaps, and regulatory burden) and assesses future trajectories, including the treaty process under HRC Resolution 26/9 and the UNGPs 10+ Roadmap. The article concludes that the UNGPs now function as a normative “operating system”: their risk-based human rights due diligence and remedy logic anchors an expanding transnational administrative space and shapes expectations that, increasingly, carry legal consequence.
Keywords: UNGPs; business and human rights